Confucianism and the Asian Martial Traditions (Revista de Artes Marciales Asiáticas, 2012)
Confucianism has been foundational in the political and social life of many Asian countries. Its influence pervades institutions and practices at every level of human activity. Martial arts have also benefited from this philosophy, as the traditional Confucian legacy continues to influence modern practices. This article briefly highlights some key figures and events, describes relevant core concepts of Confucian philosophy, and then shows exemplary applications to martial arts today. Modern martial artists can gain understanding of the traditional Confucian insights that deepen the significance of contemporary martial arts.